Fatigue analysis of propulsion shafting system with bending-torsion coupled loads - He, Yawei (2017)
With development of conventional VLOG, VLCC and 10000 TEU Container ship, the distance between shaft bearings increases and thus leads to the decrease of shaft stiffness, which has a negative effect on shaft stress. Increased propeller excitation force, induced by improved thrust power, also leads to the worse shaft vibration. In addition, a heavy propeller has a negative effect on shaft line. Therefore, it is necessary to investigate on the fatigue life of propulsion shaft, which holds a key to ship design and ship safety.